International Student Mobility Models for Enhancing Islamic Higher Education Competitiveness in ASEAN - Sururin Sururin; Sitti Aminah; Siti Khadijah; Rusmin Tumanggor; Zahara Zahara; Arif Ramadhan; Yokha Latief Ramadhan (Pascasarjana Universitas KH. Abdul Chalim, 2026)
The internationalization of higher education constitutes a strategic agenda in the development of Islamic educational institutions across the ASEAN region. This study aims to examine the policies and implementation of International Student Mobility (ISM) programs at the ministerial level and within Islamic higher education institutions in Indonesia, comparing them with their counterparts in Malaysia and Brunei Darussalam, while simultaneously formulating an effective ISM model to enhance the competitiveness of Islamic higher education institutions in ASEAN. This research employed a qualitative approach with a multi-site study design. Data were collected through in-depth interviews, direct observation, Focus Group Discussions, and document analysis across eleven institutions, comprising five Islamic universities, four public universities, and two overseas institutions. The findings reveal that ISM programs at Islamic higher education institutions can be classified into six categories: international study programs, teaching practice, community service, internship, international forum participation, and international exhibition. Key success factors include leadership commitment, supportive institutional policies, international partnerships, and language competency development. Major challenges encompass limited funding, language barriers, and complex administrative procedures. This study contributes to filling the literature gap regarding contextual ISM models for Islamic higher education institutions by proposing a model framework that integrates Islamic values, inter-institutional cooperation, and flexible credit recognition systems. These findings are significant as a policy foundation for the sustainable development of internationalization within Islamic higher education institutions across the ASEAN region.